High-strength and high-toughness polyetherimide modified adhesive and preparation method thereof
By preparing high-strength, high-tough polyetherimide modified adhesive, the toughness and strength of the adhesive are significantly improved by using the synergistic effect of materials such as polyetherimide and nitrile rubber, and the toughness and strength of the existing adhesives are solved in toughness and The strength deficiency has achieved higher mechanical properties and heat resistance.
Patent Information
- Application Number
- CN202510059148.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The adhesives of existing three-layer flexible copper clad plates do not perform well in terms of toughness and strength, resulting in poor flexibility of copper clad plates, especially when they are subjected to large stresses, which affects their reliability and service life.
Using high-strength and high-tough polyetherimide modified adhesive, epoxy resin, polyetherimide, curing agent, flame retardant, nitrile rubber, silane coupling agent, PEI@CNT and tannin acid, etc. Components, synergistically enhance the mechanical properties and heat resistance of the adhesive.
The elongation and breaking strength of the adhesive has been significantly improved. Compared with pure epoxy resin adhesive, the elongation of the break has been increased by more than 126%, and the breaking strength has been increased by more than 32%, while maintaining good high temperature resistance. .
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and in particular to a high-strength and high-toughness polyetherimide modified adhesive and a preparation method thereof. Background Art
[0002] The three-layer flexible copper clad laminate is a composite of an insulating base film, a metal copper foil and an adhesive. Compared with the rigid copper clad laminate, it is thin, light and flexible. Flexible printed circuit boards using three-layer flexible copper clad laminates as substrate materials are widely used in electronic products such as mobile phones, digital cameras, digital video cameras, automotive satellite positioning devices, LCD TVs, and laptop computers. The quality of the adhesive of the three-layer flexible copper clad laminate directly affects the performance of the copper clad laminate. Therefore, the three-layer flexible copper clad laminate is also called an adhesive-type flexible copper clad laminate. The research and development of adhesives with excellent performance, such as high toughness, high strength, and heat resistance, is very important. At present, most of the adhesives used for copper clad laminates are epoxy resin adhesives. Although they are resistant to high temperatures, they have poor toughness and strength, and the final copper clad laminates have poor flexibility.
[0003] In the prior art, in order to improve the performance of three-layer flexible copper clad laminates, a variety of methods are usually used to improve adhesives. Common methods include using different types of resins, such as epoxy resins, polyurethane resins, and acrylic resins, and improving the performance of adhesives by adjusting the formula ratio and adding various additives. For example, adding a toughening agent can improve the toughness of the adhesive, while adding a filler can enhance its mechanical properties. In addition, there are some methods to optimize the performance of adhesives by changing the production process, such as using different curing processes, pretreatment processes, etc. These methods have improved the performance of adhesives to a certain extent, but there are still some shortcomings.
[0004] Although the above method can improve the performance of the adhesive to a certain extent, it still has obvious defects. Existing adhesives are mainly based on epoxy resins. Although they have good high temperature resistance, they perform poorly in terms of toughness and strength, resulting in poor flexibility of the final copper clad laminate. Especially in applications that need to withstand greater stress, the insufficient performance of this adhesive will lead to reduced reliability and service life of the copper clad laminate. Therefore, the development of a new adhesive that can maintain high temperature resistance and significantly improve toughness and strength has become a technical problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a high-strength and high-toughness polyetherimide modified adhesive and a preparation method thereof.
[0006] In the first aspect, the present application provides a high-strength and high-toughness polyetherimide modified adhesive. The raw materials used include the following components, by weight: 42-48 parts of epoxy resin; 35-60 parts of polyetherimide; 18-22 parts of curing agent; 10-11 parts of flame retardant; 7-9 parts of nitrile rubber; 0.8-1.2 parts of silane coupling agent; 1.3-1.4 parts of PEI@CNT; and 1.5-2.0 parts of tannic acid.
[0007] By adopting the above technical scheme, the present application firstly utilizes the excellent heat resistance and mechanical strength of polyetherimide, which can maintain good performance in high temperature environment, while nitrile rubber can significantly improve the toughness of the composite material, and adds a certain amount of PEI@CNT and tannic acid, wherein PEI@CNT can form stable chemical bonds and hydrogen bonds with epoxy resin to enhance the interfacial bonding effect, and tannic acid has a unique highly branched spherical structure and a large number of active phenolic hydroxyl groups, which can not only promote the curing and cross-linking reaction of epoxy resin, but also improve the interfacial interaction with the matrix, adjust the cross-linking density, and synergistically enhance the effectiveness of multiple substances, so that the high-strength and high-toughness polyetherimide modified adhesive can maintain high temperature resistance while having higher elongation at break and fracture strength. Experimental data show that the adhesive of the present application has an elongation at break of more than 126% and a fracture strength of more than 32% compared with the existing pure epoxy resin adhesive.
[0008] The epoxy resin of the present application is EP-160, the curing agent is 4,4-diaminodiphenyl sulfone, the flame retardant is 1:1 aluminum hydroxide and hexaphenoxy cyclotriphosphazene, and the silane coupling agent is KH-550. The above substances are only used as examples and cannot limit the protection scope of the present application in turn. Therefore, those skilled in the art can reasonably replace different substances according to actual conditions.
[0009] Preferably, the raw materials used include the following components by weight: 45 parts of epoxy resin; 50 parts of polyetherimide; 20 parts of curing agent; 11 parts of flame retardant; 8 parts of nitrile rubber; 1 part of silane coupling agent; 1.35 parts of PEI@CNT; and 1.8 parts of tannic acid.
[0010] By adopting the above technical scheme, the ratio of each component is precisely optimized, especially the specific ratio of epoxy resin, polyetherimide, curing agent, flame retardant, nitrile rubber, silane coupling agent, PEI@CNT and tannic acid, which ensures that the final prepared adhesive not only has high strength and high toughness, but also has good heat resistance. The ratio specified in this application can give full play to the reinforcing effect of polyetherimide, while ensuring the high temperature resistance of epoxy resin. The reasonable addition of curing agent and flame retardant further improves the stability and safety of the adhesive. The appropriate use of nitrile rubber and silane coupling agent significantly improves the flexibility and adhesion of the adhesive. The specific amount of PEI@CNT and tannic acid effectively enhances the overall mechanical properties and heat resistance stability of the adhesive. The synergistic effect between these components increases the elongation at break of the modified rubber by 134% and the breaking strength by 36.5%.
[0011] Preferably, the PEI@CNT is prepared by the following method: carboxylated carbon nanotubes and polyethyleneimine in a weight ratio of 1:(45-50) are mixed and dispersed in water, reacted at a temperature of 110-130°C, filtered to obtain a solid, washed, and vacuum dried to obtain PEI@CNT.
[0012] By adopting the above-mentioned technical scheme, the present application mixes carboxylated carbon nanotubes and polyethyleneimine in water and reacts them at a specific temperature, so that the polyethyleneimine can form a coating layer on the surface of the carbon nanotubes, which not only improves the hydrophilicity of the carbon nanotubes, but also enhances its compatibility with the matrix material, which helps to improve the strength and toughness of the final adhesive, so that it can still maintain good mechanical properties in a high temperature environment.
[0013] Preferably, the raw materials used also include 2-3 parts by weight of phenolphthalein polyarylethersulfone.
[0014] Preferably, the amount of phenolphthalein polyarylethersulfone added is 2.7 parts.
[0015] Preferably, the phenolphthalein polyarylethersulfone is prepared by the following method: phenolphthalein and 4,4-dichlorodiphenylsulfone in a weight ratio of (15-16):12.7 are dispersed in an organic solvent, a catalyst is added, the mixture is reacted at a temperature of 125-135°C, the temperature is raised to 160-180°C and the reaction is continued, the mixture is precipitated with water, a solid is obtained by filtering, the solid is crushed, washed, and vacuum dried to obtain the phenolphthalein polyarylethersulfone.
[0016] By adopting the above technical solution, the present application obtains phenolphthalein polyarylethersulfone, whose plastic segment can improve the impact resistance of the system by absorbing energy and dispersing stress. It has good compatibility with epoxy resin and can form a uniform dispersed phase in the epoxy resin matrix, which helps to improve the overall performance of the composite material. At the same time, due to its excellent thermal stability, the modified epoxy resin can still maintain good mechanical properties under high temperature conditions. The present application also strictly controls the amount of addition, and finally obtains a high-strength and high-toughness polyetherimide modified adhesive with an elongation at break increased by 145% and a fracture strength increased by 40%.
[0017] In a second aspect, the present application provides a method for preparing a high-strength and high-toughness polyetherimide modified adhesive, comprising the following steps: S1, ultrasonically mixing epoxy resin, PEI@CNT and tannic acid, and then heating and vacuuming to form a uniform solution; S2, dispersing a curing agent, a flame retardant, a nitrile rubber, and a silane coupling agent in butanone and N,N-dimethylformamide in a weight ratio of (10-11):3, and mixing with the uniform solution obtained in step S1, wherein the weight ratio of nitrile rubber to butanone is 0.4:(10-11); S3, dispersing polyetherimide in tetrahydrofuran and N-methylpyrrolidone in a weight ratio of (4-6):(4-6) to obtain a polyetherimide solution with a concentration of 16-25wt%, and then stirring evenly at a temperature of 50-70°C, and finally blending it with the result of step S2, and stirring at this temperature for 1-3h to obtain a high-strength and high-toughness polyetherimide modified adhesive.
[0018] Preferably, in step S1, phenolphthalein polyarylethersulfone is further added and mixed with the epoxy resin, PEI@CNT and tannic acid.
[0019] Preferably, in step S3, the concentration of the polyetherimide solution is 22 wt %.
[0020] Preferably, in step S3, the stirring temperature is 60° C., and the stirring time for blending with the product obtained in step S3 is 2 h.
[0021] By adopting the above technical scheme, the preparation method can effectively improve the comprehensive performance of polyetherimide modified adhesive. Specifically, by fully mixing epoxy resin, PEI@CNT, tannic acid and phenolphthalein polyarylethersulfone under ultrasound and vacuum treatment, the uniform dispersion of the components is ensured, thereby improving the toughness and strength of the adhesive. At the same time, by controlling the dispersion conditions of curing agent, flame retardant, nitrile rubber and silane coupling agent, the mechanical properties and heat resistance of the adhesive are further optimized. In addition, the concentration of the polyetherimide solution and the selection of stirring conditions ensure the stability and consistency of the final product, so that it can still maintain excellent mechanical properties under high temperature environment.
[0022] In summary, this application has the following beneficial technical effects: 1. The present application firstly utilizes the excellent heat resistance and mechanical strength of polyetherimide, which can maintain good performance under high temperature environment, while nitrile rubber can significantly improve the toughness of the composite material, and adds a certain amount of PEI@CNT and tannic acid, wherein PEI@CNT can form stable chemical bonds and hydrogen bonds with epoxy resin to enhance the interfacial bonding effect, and tannic acid has a unique highly branched spherical structure and a large number of active phenolic hydroxyl groups, which can not only promote the curing and cross-linking reaction of epoxy resin, but also improve the interfacial interaction with the matrix, adjust the cross-linking density, and synergistically enhance the effectiveness of multiple substances, so that the high-strength and high-toughness polyetherimide modified adhesive can maintain high temperature resistance while having higher elongation at break and fracture strength. Experimental data show that the elongation at break of the adhesive of the present application is increased by more than 126% and the fracture strength is increased by more than 32% compared with the existing pure epoxy resin adhesive; 2. The plastic segment of the phenolphthalein polyarylethersulfone of the present application can improve the impact resistance of the system by absorbing energy and dispersing stress. It has good compatibility with epoxy resin and can form a uniform dispersed phase in the epoxy resin matrix, which helps to improve the overall performance of the composite material. At the same time, due to its excellent thermal stability, the modified epoxy resin can still maintain good mechanical properties under high temperature conditions. The present application also strictly controls the amount of addition, and finally obtains a high-strength and high-toughness polyetherimide modified adhesive with an elongation at break increased by 145% and a fracture strength increased by 40%. DETAILED DESCRIPTION
[0023] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Polyethyleneimine was purchased from Shanghai Aladdin, MW 70000; Carboxylated carbon nanotubes were purchased from Jiangsu Xianfeng Nanotechnology Co., Ltd., with a diameter of 4-6 mm, a length of 10-20 μm, and an oxygen content of 6.6 wt %; Phenolphthalein was purchased from Tianjin Damao Chemical Reagent Factory; 4,4-Dichlorodiphenyl sulfone was purchased from Jiangsu Zhonggao Chemical Co., Ltd.; Anhydrous potassium carbonate, dimethyl sulfoxide, and toluene were purchased from Sinopharm Chemical Reagent Co., Ltd.; Epoxy resin was purchased from Hansen Momentive, USA, EP-160; Tannic acid was purchased from Shanghai Aladdin; 4,4-Diaminodiphenyl sulfone was purchased from MacLean; Hexaphenoxycyclotriphosphazene was purchased from Guangzhou Yinyuan New Materials Co., Ltd.; Nitrile rubber was purchased from Hangzhou Yusheng Environmental Technology Co., Ltd.; Silane coupling agent KH-550 was purchased from Jinan Rongguang Chemical Co., Ltd., pH 5-7; Commercially available adhesives were purchased from Jinan Shanbo Trading Co., Ltd.
[0024] The present application is further described in detail below in conjunction with embodiments and comparative examples.
[0025] Preparation Example 1.1 The preparation method of PEI@CNT comprises the following steps: Polyethyleneimine was dissolved in water to form a polyethyleneimine solution with a concentration of 50 g / L, and then carboxylated carbon nanotubes were added until its concentration was 1 g / L. The solution was placed in an oil bath and condensed and refluxed at 120°C for 12 hours. The solid was obtained by vacuum filtration, washed with deionized water 5 times to remove excess polyethyleneimine, and freeze-dried in a vacuum freeze dryer to obtain PEI@CNT.
[0026] Preparation Example 1.2 The preparation method of PEI@CNT comprises the following steps: Polyethyleneimine was dissolved in water to form a polyethyleneimine solution with a concentration of 45 g / L, and then carboxylated carbon nanotubes were added until the concentration was 1 g / L. The solution was placed in an oil bath and condensed and refluxed at 120°C for 12 hours. The solid was obtained by vacuum filtration, washed with deionized water 5 times to remove excess polyethyleneimine, and freeze-dried in a vacuum freeze dryer to obtain PEI@CNT.
[0027] Preparation Example 2.1 The preparation method of phenolphthalein polyarylethersulfone comprises the following steps: 1.5 kg of phenolphthalein, 1.27 kg of 4,4-dichlorodiphenyl sulfone, 0.83 kg of anhydrous potassium carbonate, 11 L of dimethyl sulfoxide and 4 L of toluene were mixed, reacted at 125°C for 2 h, the toluene was evaporated, the temperature was raised to 160°C and the reaction was continued for 3 h, then poured into deionized water for precipitation, filtered to obtain a solid, crushed and washed with deionized water for 3 times, then washed with ethanol for 3 times, vacuum dried for 24 h, and ball milled to obtain phenolphthalein polyarylethersulfone.
[0028] Preparation Example 2.2 The preparation method of phenolphthalein polyarylethersulfone comprises the following steps: 1.6 kg of phenolphthalein, 1.27 kg of 4,4-dichlorodiphenyl sulfone, 0.83 kg of anhydrous potassium carbonate, 11 L of dimethyl sulfoxide and 4 L of toluene were mixed, reacted at 135°C for 2 h, the toluene was evaporated, the temperature was raised to 180°C and the reaction was continued for 3 h, then poured into deionized water for precipitation, filtered to obtain a solid, crushed and washed with deionized water for 3 times, then washed with ethanol for 3 times, vacuum dried for 24 h, and ball milled to obtain phenolphthalein polyarylethersulfone.
[0029] Example 1.1 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive comprises the following steps: S1, 4.2 kg of epoxy resin, 0.13 kg of PEI@CNT prepared in Preparation Example 1.1 and 0.2 kg of tannic acid were ultrasonically mixed, and then heated and vacuumed to form a uniform solution; S2, 1.8 kg curing agent (4,4-diaminodiphenyl sulfone), 1.1 kg flame retardant (0.55 kg aluminum hydroxide and 0.55 kg hexaphenoxy cyclotriphosphazene), 0.9 kg nitrile rubber, 120 g silane coupling agent KH-550 are dispersed in a mixed solution of 20 kg butanone and 3 kg N, N-dimethylformamide, and mixed with the uniform solution obtained in step S1, the mixing temperature is 25 ° C, and the mixing speed is 200 rpm; S3, dispersing 6 kg of polyetherimide in tetrahydrofuran and N-methylpyrrolidone in a weight ratio of 4:6 to obtain a polyetherimide solution with a concentration of 16 wt%, then stirring it evenly at a temperature of 70 ° C, and finally blending it with the result of step S2, keeping warm and stirring for 1 hour to obtain a high-strength and high-toughness polyetherimide modified adhesive.
[0030] Example 1.2 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive comprises the following steps: S1, 4.8 kg of epoxy resin, 0.14 kg of PEI@CNT prepared in Preparation Example 1.2 and 0.15 kg of tannic acid were ultrasonically mixed, and then heated and vacuumed to form a uniform solution; S2, dispersing 2.2 kg of curing agent (4,4-diaminodiphenyl sulfone), 1 kg of flame retardant (0.5 kg of aluminum hydroxide and 0.5 kg of hexaphenoxy cyclotriphosphazene), 0.7 kg of nitrile rubber, and 80 g of silane coupling agent KH-550 in a mixed solution of 19.25 kg of butanone and 5.25 kg of N,N-dimethylformamide, and mixing with the uniform solution obtained in step S1, the mixing temperature is 25° C., and the mixing speed is 200 rpm; S3, dispersing 3.5 kg of polyetherimide in tetrahydrofuran and N-methylpyrrolidone in a weight ratio of 6:4 to obtain a polyetherimide solution with a concentration of 25 wt%, then stirring it evenly at a temperature of 50 ° C, and finally blending it with the result of step S2, keeping warm and stirring for 3 hours to obtain a high-strength and high-toughness polyetherimide modified adhesive.
[0031] Example 1.3 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive comprises the following steps: S1, 4.5 kg of epoxy resin, 0.14 kg of PEI@CNT prepared in Preparation Example 1.1 and 0.15 kg of tannic acid were ultrasonically mixed, and then heated and vacuumed to form a uniform solution; S2, dispersing 2 kg of curing agent (4,4-diaminodiphenyl sulfone), 1.1 kg of flame retardant (0.55 kg of aluminum hydroxide and 0.55 kg of hexaphenoxy cyclotriphosphazene), 0.8 kg of nitrile rubber, and 100 g of silane coupling agent KH-550 in a mixed solution of 19.5 kg of butanone and 5.5 kg of N,N-dimethylformamide, and mixing with the uniform solution obtained in step S1, the mixing temperature is 25 ° C, and the mixing speed is 200 rpm; S3, dispersing 5 kg of polyetherimide in tetrahydrofuran and N-methylpyrrolidone in a weight ratio of 5:5 to obtain a polyetherimide solution with a concentration of 20 wt%, then stirring it evenly at a temperature of 50 ° C, and finally blending it with the result of step S2, keeping warm and stirring for 3 hours to obtain a high-strength and high-toughness polyetherimide modified adhesive.
[0032] Example 2.1 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.2 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0033] Example 2.2 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.3 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0034] Example 2.3 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.22 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0035] Example 2.4 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.24 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0036] Example 2.5 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.27 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0037] Example 2.6 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 1.3 in that, in step S1, 0.29 kg of phenolphthalein polyarylethersulfone prepared in Preparation Example 2.1 is also added, and the rest is the same as Example 1.3.
[0038] Example 3.1 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 2.5 in that, in step S3, the concentration of the polyetherimide solution is 18wt%, and the rest is the same as Example 2.5.
[0039] Example 3.2 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 2.5 in that in step S3, the concentration of the polyetherimide solution is 20wt%, and the rest is the same as Example 2.5.
[0040] Example 3.3 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 2.5 in that in step S3, the concentration of the polyetherimide solution is 22wt%, and the rest is the same as Example 2.5.
[0041] Example 3.4 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 2.5 in that in step S3, the concentration of the polyetherimide solution is 24wt%, and the rest is the same as Example 2.5.
[0042] Example 4 A method for preparing a high-strength and high-toughness polyetherimide modified adhesive is different from Example 3.3 in that, in step S3, the stirring temperature is 60°C, and the stirring time for blending with the result of step S3 is 2 hours, and the rest is the same as Example 3.3.
[0043] Comparative Example 1 The difference from Example 1.3 is that the nitrile rubber in step S2 is removed, the amount of epoxy resin used in step S1 is 5.1 kg, and the rest is the same as Example 1.3.
[0044] Comparative Example 2 The difference from Example 1.3 is that step S3 is removed, and the rest is the same as Example 1.3.
[0045] Comparative Example 3 The difference from Example 1.3 is that the tannic acid in step S1 is removed, the amount of PEI@CNT prepared in Preparation Example 1.1 is 0.33 kg, and the rest is the same as Example 1.3.
[0046] Comparative Example 4 The difference from Example 1.3 is that the PEI@CNT prepared in Preparation Example 1.1 in step S1 is removed, the amount of tannic acid used is 0.33 kg, and the rest is the same as Example 1.3.
[0047] Comparative Example 5 The difference from Example 1.3 is that the PEI@CNT prepared in Preparation Example 1.1 in step S1 is replaced by carboxylated carbon nanotubes, and the rest is the same as Example 1.3.
[0048] Performance Testing First, pour the commercially available adhesive based on epoxy resin into a preheated polytetrafluoroethylene mold coated with a release agent, put it into a vacuum oven at 90°C to remove bubbles, and then cure it at a curing temperature of 165°C for 30 minutes. After curing, demould it to obtain the standard dumbbell-shaped casting specimen required for performance testing, with a total length of 100 mm, a width of 25 mm ± 0.10 mm, and a thickness of 25 mm ± 0.25 mm. The high-strength and high-toughness polyetherimide modified adhesive obtained in the embodiment and the comparative example is poured into a polytetrafluoroethylene mold coated with a release agent and preheated, and placed in a vacuum oven at 90°C to evacuate and remove bubbles, followed by curing at a curing temperature of 165°C for 30 minutes. After curing, the mold is demolded to obtain the standard dumbbell-shaped casting specimen required for performance testing, with a total length of 100 mm, a width of 25 mm±0.10 mm, and a thickness of 25 mm±0.25 mm, and the following tests are performed.
[0049] The tensile tester with a measuring range set to a maximum of 980N and an accuracy set to ±1% was used to perform a tensile test on the above-mentioned specimens. The tensile speed was 1mm / min, and the elongation at break and the fracture strength were recorded. The elongation at break and the fracture strength of the commercially available epoxy resin adhesive were used as a comparison. The improvement ratio of the elongation at break and the fracture strength of the examples of the present application and the comparative examples was recorded and recorded in Table 1; The glass transition temperature (T g ), recorded in Table 1; The peel strength of the above-mentioned specimens was tested according to GB / T7122-1996, with a loading speed of 30 mm / min, and the results are recorded in Table 1.
[0050] Table 1 Performance test table
[0051] Data Analysis: As can be seen from Table 1, the elongation at break of Examples 1.1-1.2 of the present application can be increased by 126-127%, the fracture strength can be increased by 32%, the glass transition temperature can be up to 356°C, and the peel strength is 1.49-1.50N / mm, which proves that the present application firstly utilizes the excellent heat resistance and mechanical strength of polyetherimide, and can maintain good performance under high temperature environment, while nitrile rubber can significantly improve the toughness of the composite material, and a certain amount of PEI@CNT and tannic acid are added, wherein PEI@CNT can form stable chemical bonds and hydrogen bonds with epoxy resin to enhance the interface bonding effect, and tannic acid has a unique highly branched spherical structure and a large number of active phenolic hydroxyl groups, which can not only promote the curing and crosslinking reaction of epoxy resin, but also improve the interface interaction with the matrix, adjust the crosslinking density, and synergistically enhance the synergy of multiple substances, so that the high-strength and high-toughness polyetherimide modified adhesive can have higher elongation at break and fracture strength while maintaining high temperature resistance; The elongation at break and the strength at break of Example 1.3 are both improved compared to those of Example 1.1, which proves that the application accurately optimizes the ratio of each component, especially the specific ratio of epoxy resin, polyetherimide, curing agent, flame retardant, nitrile rubber, silane coupling agent, PEI@CNT and tannic acid, to ensure that the final prepared adhesive not only has high strength and high toughness, but also has good heat resistance. The difference between Examples 2.1-2.6 and Example 1.3 is that phenolphthalein polyarylethersulfone is further added, and the elongation at break and the strength at break are improved compared with those in Example 1.3, which proves that the plastic segment of phenolphthalein polyarylethersulfone can improve the impact resistance of the system by absorbing energy and dispersing stress, and it has good compatibility with epoxy resin and can form a uniform dispersed phase in the epoxy resin matrix, which helps to improve the overall performance of the composite material. At the same time, due to its excellent thermal stability, the modified epoxy resin can still maintain good mechanical properties under high temperature conditions; The difference between Examples 3.1-3.4 and Example 2.5 lies in the concentration of the polyetherimide solution, wherein Example 3.3 has the highest elongation at break and the highest strength at break, proving that the present application ensures the stability and consistency of the final product by strictly controlling the concentration of the polyetherimide solution, so that the product can still maintain excellent mechanical properties in a high temperature environment; The difference between Example 4 and Example 3.3 lies in the stirring temperature and time. The elongation at break and the breaking strength at break are both improved, which proves that the present application ensures the stability and consistency of the final product by strictly controlling the stirring conditions, so that it can still maintain excellent mechanical properties in a high temperature environment; The improvement rate of elongation at break and the improvement rate of breaking strength of comparative examples 1-5 are lower than those of embodiment 1.1, which proves that the present application firstly utilizes the excellent heat resistance and mechanical strength of polyetherimide, which can maintain good performance in high temperature environment, while nitrile rubber can significantly improve the toughness of the composite material, and a certain amount of PEI@CNT and tannic acid are added, among which PEI@CNT can form stable chemical bonds and hydrogen bonds with epoxy resin to enhance the interfacial bonding effect, and tannic acid has a unique highly branched spherical structure and a large number of active phenolic hydroxyl groups, which can not only promote the curing and cross-linking reaction of epoxy resin, but also improve the interfacial interaction with the matrix, adjust the cross-linking density, and synergistically enhance the effectiveness of multiple substances, so that the high-strength and high-toughness polyetherimide modified adhesive can have higher elongation at break and breaking strength while maintaining high temperature resistance.
[0052] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A high-strength and high-toughness polyetherimide modified adhesive, characterized in that: The raw materials used include the following components by weight: 42-48 parts of epoxy resin; 35-60 parts of polyetherimide; 18-22 parts of curing agent; 10-11 parts of flame retardant; 7-9 parts of nitrile rubber; 0.8-1.2 parts of silane coupling agent; 1.3-1.4 parts of PEI@CNT; and 1.5-2.0 parts of tannic acid.
2. The high-strength and high-toughness polyetherimide modified adhesive according to claim 1, characterized in that: The raw materials used include the following components by weight: 45 parts of epoxy resin; 50 parts of polyetherimide; 20 parts of curing agent; 11 parts of flame retardant; 8 parts of nitrile rubber; 1 part of silane coupling agent; 1.35 parts of PEI@CNT; and 1.8 parts of tannic acid.
3. The high-strength and high-toughness polyetherimide modified adhesive according to claim 1, characterized in that: The PEI@CNT is prepared by the following method: Carboxylated carbon nanotubes and polyethyleneimine in a weight ratio of 1:(45-50) are mixed and dispersed in water, and reacted at a temperature of 110-130°C, and the solid is filtered, washed, and vacuum dried to obtain PEI@CNT.
4. The high-strength and high-toughness polyetherimide modified adhesive according to claim 1, characterized in that: The raw materials used also include 2-3 parts by weight of phenolphthalein polyarylethersulfone.
5. A high-strength and high-toughness polyetherimide modified adhesive according to claim 4, characterized in that: The added amount of the phenolphthalein polyarylethersulfone is 2.7 parts.
6. The high-strength and high-toughness polyetherimide modified adhesive according to claim 4, characterized in that: The phenolphthalein polyarylethersulfone is prepared by the following method: Change the weight ratio to (15-16): 12.7 of phenolphthalein and 4,4-dichlorodiphenyl sulfone are dispersed in an organic solvent, a catalyst is added, and the mixture is reacted at 125-135°C, and the mixture is heated to 160-180°C to continue the reaction, and the mixture is precipitated with water, filtered to obtain a solid, crushed, washed, and vacuum dried to obtain phenolphthalein polyarylethersulfone.
7. A method for preparing the high-strength and high-toughness polyetherimide modified adhesive according to claim 1, characterized in that: The following steps are involved: S1, mixing epoxy resin, PEI@CNT and tannic acid by ultrasonication, and then heating and vacuuming to form a uniform solution; S2, dispersing the curing agent, flame retardant, nitrile rubber, and silane coupling agent in butanone and N,N-dimethylformamide in a weight ratio of (10-11):3, and mixing with the uniform solution obtained in step S1, wherein the weight ratio of the nitrile rubber to butanone is 0.4:(10-11); S3, dispersing polyetherimide in tetrahydrofuran and N-methylpyrrolidone in a weight ratio of (4-6): (4-6) to obtain a polyetherimide solution with a concentration of 16-25wt%, then stirring it evenly at a temperature of 50-70°C, and finally blending it with the result of step S2, and stirring it at this temperature for 1-3h to obtain a high-strength and high-toughness polyetherimide modified adhesive.
8. The method for preparing the high-strength and high-toughness polyetherimide modified adhesive according to claim 7, characterized in that: In the step S1, phenolphthalein polyarylethersulfone is also added and mixed with epoxy resin, PEI@CNT and tannic acid.
9. The method for preparing the high-strength and high-toughness polyetherimide modified adhesive according to claim 7, characterized in that: In the step S3, the concentration of the polyetherimide solution is 22 wt %.
10. The method for preparing the high-strength and high-toughness polyetherimide modified adhesive according to claim 7, characterized in that: In the step S3, the stirring temperature is 60° C., and the stirring time for blending with the product obtained in step S3 is 2 hours.
Citation Information
Patent Citations
Method for preparing functionalized carbon nanotube based on polyethyleneimine
CN101565180A
High temperature-resistant adhesive as well as preparation method and application thereof
CN109266297A
Epoxy resin composition, prepreg and fiber-reinforced composite material
JP2006219513A